Calcium-Rich Biochar Derived from Cactus Feedstock and Its Efficient Adsorption Properties for Industrial Dye - Assia Maaoui; Raouia Chagtmi; Barbara Apicella; Francesca Cerciello; Osvalda Senneca; Aida Ben Hassen Trabelsi (Applied Sciences)
The leather industries are large producers of industrial wastewater. The present work investigated the performance of calcium-rich biochar derived from cactus cladodes (CCB) as an adsorbent in the treatment of this wastewater. Biochar samples (CCB500, CCB600, and CCB700) were produced by slow pyrolysis at 500, 600, and 700 °C and tested as adsorbents of Repanil Blue (RB) dye. The tests were carried out under various experimental conditions. The RB dye removal increased with the contact time, adsorbent dose, and concentration. With dye concentrations between 10 and 125 mg/L, removal efficiencies of 80, 80 and 100% were reached using CCB500, CCB600, and CCB700, respectively. The Langmuir model and the pseudo-second-order model described chemisorption with a high correlation factor (R2). The highest adsorption capacity of 56 mg/g was obtained with CCB700 within 5 min. The results strongly suggest that calcium-rich biochars are promising adsorbents for the removal of RB dye from aqueous solutions.